Combinatorial development and high throughput materials characterisation of steels - Steve Brown (Ironmaking & Steelmaking, 2015)
A series of small iron specimens with minor additions of C, Si and Mn were manufactured via induction melting and characterised using a high throughput methodology. The aim was to analyse the high throughput approach itself, not the effects of minor additions to steel. Despite their small size, the trends in measured standard mechanical properties were consistent with published data, and target alloy compositions were achieved to a sufficient degree of accuracy. This is most encouraging as the experimental approaches described here delivered results in a very short time frame, with time per composition estimated to be < 2 h per sample. Such an approach would appear to be an excellent precursor to more traditional, expensive and time consuming alloy development methods used by industry. Limitations of the methodology are described, and key bottlenecks are identified. However, the use of small specimens to quantify trends in properties of steels and identify possible new alloys is potentially a valuable addition to the development of new steels.